Synthesis and modification of bio-derived antibacterial Ag and ZnO nanoparticles by plants, fungi, and bacteria. Issue 8 (August 2021) - Alavi, Mehran; Nokhodchi, Ali
Graphical abstract: Highlights: Plants, bacteria, and fungi contribute in the synthesis of Ag and ZnO nanoparticles (NPs). NPs have shown promising antibacterial activity towards multidrug-resistant bacteria. Gram-negative bacteria show more sensitivity to NPs than do Gram-positive bacteria. Non-uniformity of nanoparticle size and shape can impact on their antibacterial potential. The role of various metabolites in controlling the properties of NPs is critical. Abstract: Ag and ZnO nanoparticles (NP) can be prepared by physical, chemical, or eco-friendly methods. The biosynthesis of metal and metal oxide NPs by plants, fungi, and bacteria could be a promising way to obtain biocompatible NPs that have desirable antibacterial activities. However, the uniformity of shape, size, and size distribution of NPs are crucial to producing significant antibacterial results, particularly in physiological conditions such as infected wounds or septicemia. In this review, we discuss recent progress and challenges in the use of novel approaches for the biosynthesis of Ag and ZnO nanoparticles that have antibacterial activities.